Slow facial signs and their psychodiagnostic value - Bida, S.; Lutsenko, O. (My University, 2018)
The current study is devoted to the identification of the scientific basis of permanent facial expression as a psychodiagnotic measure. The aim of the research is to investigate relationships between slow facial signs (SFS) and emotional personality traits with taking into account age and gender on the sample of Eastern Ukrainians (201 participants). To that end, we measured participants’ personality traits levels and photographed their neutral faces in order to identify any SFS on the photographs of their faces. The test battery included the Spielberger state-trait anxiety inventory, Taylor manifest anxiety scale, Buss-Durkey hostility inventory, Vasserman social frustration questionnaire, Vasserman neuroticism scale, Personal differential inventory, “Draw-A-Person” and “Draw-A-Person-In-The-Rain” projective tests. We applied Facial Action Coding System (Ekman, Friesen, & Hager) to identify and interprete SFS on the photographs. We found that the most part of revealed SFS relates to anger (12) and sadness (11). The fewest number of revealed SFS relates to disgust / contempt (5), fear (4) and happiness (4). The elder a person becomes the more increasing number of SFS of sadness (highest rates), anger (lower rates), fear (still lower) and happiness (lowest rates) is expected in one’s face. There are no significant differences in manifesting SFS between men and women. We found significant correlations between relevant SFS and traits anxiety, depression, and agressiveness (in its guilt and resentment aspects).
Повільні сигнали обличчя та їх психодіагностичне значення
Визначення наукової основи психодіагностики через постійні вирази обличчя є проблемою, якій присвячено це дослідження. Метою дослідження є аналіз зв'язків між повільними сигналами обличчя (ПСО) та емоційними рисами особистості з урахуванням віку та статі у вибірці східних українців (201 учасник). Щоб виявити ПСО були зняті фотографії нейтральних облич учасників. Рівень рис оцінювався за допомогою Опитувальника тривожності Спілбергера, шкали тривожності Тейлор, тесту ворожості Басса-Дарки, опитувальника соціальної фрустрації Вассермана, шкали нейротизму Вассермана, особистісного диференціалу, проективних тестів «Намалюй людину» та «Намалюй людину під дощем». Для виявлення значень ПСО з фотографій була застосована Система кодування обличчя (Ekman, Friesen, & Hager). Було виявлено, що більша частина виявлених ПСО відноситься до гніву (12) та суму (11). Найменша кількість виявлених ПСО належить до огиди / презирства (5), страху (4) та щастя (4). З віком на обличчі людей зростає кількість ПСО, що передають сум (найвищий ступінь), гнів (трохи менше), страх (менше) і щастя (найрідше). Відсутні суттєві відмінності у прояві ПСО між чоловіками та жінками. Виявлено значні кореляції відповідних ПСО з тестовими показниками тривожності, депресії та агресивності (у її аспектах почуття провини та образи). Ключові слова: вирази обличчя, повільні сигнали обличчя, емоційні риси, тривожність, депресія, агресивність, щастя.
Keywords: facial expression; happiness; slow facial signs; emotional traits; anxiety; depressiveness; aggressiveness